Food Insecurity in an Urban Pregnancy Cohort - Sullivan, Kirby; St John, Meghan; DeFranco, Emily; Kelly, Elizabeth (American Journal of Perinatology, 2021)
Objective Food insecurity is a prominent problem and has been implicated in adverse maternal and neonatal outcomes. This study aims to describe the food insecure population in an urban academic health center perinatal cohort.Study Design We enrolled 451 postpartum inpatients at the University of Cincinnati Medical Center who completed a questionnaire and were then categorized as food insecure based on U.S. Department of Agriculture standardized survey questions. Generalized linear models estimated the relative influence of maternal characteristics on food insecurity.Results Among the study population (n = 426), 18.6% (95% confidence interval: 15.2–22.4%) were classified as food insecure. Factors with increased adjusted relative risk on food insecurity include annual household income <$40,000, obesity, and smoking. Food insecure women also reported lower levels of love, satisfaction, and joy, and higher levels of despair.Conclusion We recommend the use of a validated screening tool on all pregnant women with the associated psychosocial stressors and social determinants of health.Key Points
Keywords: food security; food insecurity; pregnancy; social determinants